Universal Basic Income: Inspecting the Mechanisms - Jaimovich, Nir; Saporta-Eksten, Itay; Setty, Ofer; Yedid-Levi, Yaniv (The Review of Economics and Statistics, 2024)
We examine the mechanisms driving the aggregate and distributional impacts of Universal Basic Income (UBI) through model analysis of various UBI programs and financing schemes. The main adverse effect is the distortionary tax increase to fund UBI, reducing labor force participation. Secondary channels are a decline in demand for self-insurance, depressing aggregate capital, and a positive income effect that further deters labor force participation. Due to these channels, introducing UBI alongside existing social programs reduces output and average welfare. Partially substituting existing programs with UBI mitigates the adverse effects, increases average welfare, but does not deliver a Pareto improvement.